2008
DOI: 10.3892/mmr.1.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of cimetidine on advanced serous ovarian carcinoma related to cyclooxygenase-2 expression

Abstract: This study was performed to identify the contribution of cimetidine to chemotherapy for epithelial ovarian carcinoma. Cimetidine was administered two weeks before surgery in combination with platinum-based chemotherapy, and the treatment was continued for two years. Cyclooxygenase-2 (COX-2) expression was also evaluated. The chemotherapy regimens did not affect patient prognosis. The effect of cimetidine was more marked in patients who showed overexpression of COX-2. Platinum-based chemotherapy combined with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…A small trial in 28 advanced serous ovarian carcinoma patients found that standard platinum-based chemotherapies augmented with CIM, at a dose of 800 mg/day, commencing 2 weeks before surgery and continuing synchronously with chemotherapy, showed statistically significant improvements in overall survival compared to platinum-based chemotherapy alone [ 66 ].…”
Section: Human Data In Cancermentioning
confidence: 99%
“…A small trial in 28 advanced serous ovarian carcinoma patients found that standard platinum-based chemotherapies augmented with CIM, at a dose of 800 mg/day, commencing 2 weeks before surgery and continuing synchronously with chemotherapy, showed statistically significant improvements in overall survival compared to platinum-based chemotherapy alone [ 66 ].…”
Section: Human Data In Cancermentioning
confidence: 99%